Extreme spindles and leukoencephalopathy after acute lymphoblastic leukemia treatment: An undescribed association - Kanda, Paulo Afonso Medeiros; Kanda, Rafael Guimarães [UNESP]; Mei, Paulo Afonso; Cury, Ivan José (Taylor & Francis, 2015)
We report a case of a child whose EEG demonstrated extreme spindles (ES) after acute lymphoblastic leukemia treatment. This finding has not been reported previously. In 1962, Gibbs and Gibbs described the ES EEG pattern due to its high amplitude (200 to 400 μV). ES are a rare spindle variant that is found in EEGs of 0.05% of normal children (average age, 3 years, with a range of 1 to 12 years), and are even rarer after 11 years. Moreover, due to changes in the white matter of the frontal lobe, ES have been associated with such conditions as cerebral palsy and mental retardation, residual brain damage, undefined infections, infantile neuroaxonal dystrophy, Menkes' kinky-hair syndrome, congenital muscular dystrophy, hydrocephalus, porencephaly, epilepsy, progressive cerebellar degeneration, and mycoplasma encephalitis. Methotrexate has a notably toxic effect on the central nervous system, with leukoencephalopathy being the most common form. In our case, frontocentral ES were associated with hyperintense lesions in the white matter of the frontal lobe. Lesional deafferentation can be the substrate for an almost continuous ES, since both initiation and termination of spindle oscillations are thought to originate in thalamocortical neurons. Thus, we postulate that in some cases a partial functional cortical differentiation could generate ES.
Keywords: EEG; EEG variant; Extreme spindles; Leukoencephalopathy; Lymphoblastic leukemia.